SOCIAL POLICIES AND IMPLEMENTATION PROBLEMS IN NIGERIA: A CASE STUDY OF DFFRI AND POLICIES BEFORE IT - EMMANUEL NJOR, PRO. OKOM; ISOMKWO, pro. ABOH FIDELIS (International Journal of Multidisciplinary Research and Studies, 2019)
No Nigerian social policy is without criticism, whether it be constructed by a professor of academic wizardry or by the most intelligent group of men in the system. Criticism is not bad in itself. What can be bad about it is the intention of the critic. If a critic sets out to criticize a social policy with a destructive disposition, this then is unprofessional and counterproductive to the very spirit that drives social policy. If, however, a social policy is objectively criticized with a view to seeing that the maker(s) of such policies improve on the quality of subsequent policies and their implementation, this then is commendable. This is an attempt to objectively criticize the Directorate for Food, Roads and Rural Infrastructure (DFFRI) of the Babangida military regime of 1985, comparing it with policies before it, with a view to highlighting the successes of the policy while exposing its failures.